Upgrading of bio-oil into advanced biofuels and chemicals. Part I. Transformation of GC-detectable light species during the hydrotreatment of bio-oil using Pd/C catalyst - Gunawan, Richard; Li, Xiang; Lievens, Caroline; Gholizadeh, Mortaza; Chaiwat, Weerawut; Hu, Xun; Mourant, Daniel; Bromly, John; Li, Chun-Zhu (Elsevier Ltd, 2013)
Bio-oil cannot be directly used as biofuel mainly due to its abundant oxygen-containing functional groups. Therefore, bio-oil must be upgraded to produce high quality biofuels. As the first part of this series, this paper reports the transformation of GC-detectable light components during the hydrotreatment of bio-oil using noble-metal catalyst Pd/C over a wide range of reaction temperature (150–300 °C). Our results show that aldehydes were easily hydrogenated, with cyclopentanone and 2-methyl cyclopentanone among the observed products. During hydrotreatment, carboxylic acids such as propionic, butanoic and pentanoic acids were also observed in the liquid products. Furthermore, evolution of propyl guaiacol, ethyl guaiacol, methyl guaiacol, guaiacol and syringol confirms the depolymerisation of the lignin-derived oligomers during the hydrotreatment of bio-oil. The hydrogenation of the phenolic compounds also took place. In addition, the FT-IR analysis of the O-containing functional groups, especially carbonyl groups, confirms the trends found by GC–MS.